Decision Support System for Final Assignment with Analytical Hierarchy Process (AHP) Method. Case Study: Informatics Engineering Faculty of Engineering, Pancasila University - Sri Rezeki Candra Nursari; Virgie Sciorra (bit-Tech, 2018)
In human life always faced with several choices. The right decision making will affect our lives in the future. In the bachelor degree program education Final Project is the closing course to get a Bachelor's degree. Many things need to be considered in determining the appropriate TA topic. Many people have a view, choose the topic of Final Assignment that is easy so easy, regardless of suitability with interests and talents. Actually this view needs to be reviewed because choosing the topic of Final Assignment has a significant impact on the lives of these students in the future. To determine the topic of Final Assignment in the Informatics Engineering Faculty of Engineering, the Pancasila University required mastering criteria, mastering memorization, mastering the count, mastering the design, value, and areas of interest. And has an alternative, namely Information Systems, Decision Support Systems using methods, Intelligent Systems/Expert Systems, Networks, Mobile Programming (Games), Mobile Programming (Applications), Use of Algorithms in Support Systems / Applications of this Decree using Analytic Hierarchy Process method for determine the exact topic of Final Assignment according to the ability of students. The AHP method refers to taking selected elective courses